2008
DOI: 10.1055/s-2007-1004572
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Levels of Tumor Necrosis Factor-α and Soluble Tumor Necrosis Factor Receptor 1 Before and After the Onset of Labor in Normal Pregnancies

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is present in human placental and uterine cells and promotes the regulation of trophoblast growth and invasion. Tumor necrosis factor receptor 1 (TNF-R1) is a receptor for TNF-alpha, and soluble TNF-R1 (sTNF-R1) is present in amniotic fluid after receptor shedding. We evaluated whether amniotic fluid TNF-alpha and sTNF-R1 levels during labor differed from those before the onset of labor in normal pregnancies. This study enrolled 34 Japanese women experiencing normal preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the amniotic membrane, apoptosis is induced by TNF-α (Menon et al 2002). Increases in TNF-α expression in amniotic fluid and apoptotic cells in the amniotic membranes are observed in patients undergoing spontaneous delivery with labor and in patients with chorioamnionitis (Hayashi et al 2008;Kataoka et al 2002;Lei et al 1996;Maymon et al 1999). AQP9 expression increases in the presence of spontaneous labor at term and chorioamnionitis (Mittal et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the amniotic membrane, apoptosis is induced by TNF-α (Menon et al 2002). Increases in TNF-α expression in amniotic fluid and apoptotic cells in the amniotic membranes are observed in patients undergoing spontaneous delivery with labor and in patients with chorioamnionitis (Hayashi et al 2008;Kataoka et al 2002;Lei et al 1996;Maymon et al 1999). AQP9 expression increases in the presence of spontaneous labor at term and chorioamnionitis (Mittal et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The incubation of isolated human neutrophils with anti-AQP9 antibodies resulted in an impaired neutrophil migration [27]. Amniotic fluid tumor necrosis factor-α (TNF-α) expression and apoptotic cells in the amniotic membrane were significantly increased in patients who underwent spontaneous labor at term, which is well-defined to implicate local and systemic activation of the inflammatory cascade, and in patients with HCA [28,29]. Given the significant role of TNF-α in inducing AQP9 expression, AQP9 might contribute to an apoptotic volume decrease of the amniotic epithelial cells initiated by TNF-α [30].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that TNF‐α concentration in the late gestation showed a negative correlation with the newborn birth weight. TNF‐α is known to be present in human placental and uterine cells and promote the regulation of trophoblast growth and invasion 27 . It may be considered a regulator of intrauterine bone development of newborns in the uncomplicated pregnancy 28 .…”
Section: Discussionmentioning
confidence: 99%